Gendering 'Thursday Night Football': Examining dialogue differences between all-female and all-male broadcast teams. Issue 3 (3rd April 2021) - Sadri, Sean R.; Bell, Travis R.; Billings, Andrew C.
ABSTRACT: On 27 September 2018, history was made when Hannah Storm and Andrea Kremer became the first all-female broadcast team to call a major professional men's team sport – a National Football League game between the Los Angeles Rams and the Minnesota Vikings. Storm provided the play-by-play and Kremer was the analyst for a 'Thursday Night Football' livestream on Amazon Prime, which was simulcast alongside a Fox television broadcast with veteran announcers Joe Buck and Troy Aikman. For viewers, the game represented seismic changes to a media landscape that had historically promoted aggression and a disruption to a sports ecosystem that routinely reinforces male-dominated gender norms. To better understand whether differences were advanced in the dialogues of the two broadcast teams, content analyses of the Amazon broadcast and the Fox broadcast were conducted. Attributes of athletic successes, failures, and physicality/personality were coded as verbal descriptors to allow comparison. A total of 777 descriptors showed significant differences in the frequency of the three classification areas, yet only one verbal descriptor difference was detected; the male team disproportionately elevated successes due to athletic ability. Results and the implications of these findings are discussed.